Membangun Community relationss Dalam Perayaan Idul Qurban - Islami, Dian Ismi; Ningsih, Cakra; Sukarni, Nurul Fadzar (Jurnal Pustaka Dianmas, 2023)
The celebration of Eid al-Adha is a unifying celebration among human beings, the meat of qurban animals is not only intended for muslim or the poor, anyone can get the meat of qurban animals. The eid al-Adha moment can also be used as an opportunity to build relationships with the community. The purpose of this activity is a form of community service carried out by the academic community of Prof. Moestopo (Religious) in accordance with the third higher education tridarma, namely community service, fostering good realtion with the community, namely the qurban animal farming community and the beneficiary community of qurban animal as a form of responsibility in transferring and informing knowledge to the public. The implementation method starts with recruiting shohibul qurban, then collaborating with the qurban animal providers and qurban slaughterers, followed by wrapping the qurban meat and distributing it to the public. The results of the implementation of this activity can synergize well with community parties, and can educate the public about the procedures fo slaughtering qurban animal that are good and in accordance with Islamic law.